A SH3_5 Cell Anchoring Domain for Non-recombinant Surface Display on Lactic Acid Bacteria - Tay, Pei Kun Richie; Lim, Pei Yu; Ow, Dave Siak-Wei (Frontiers in Bioengineering and Biotechnology, 2021)
Lactic acid bacteria (LAB) are a group of gut commensals increasingly recognized for their potential to deliver bioactive molecules in vivo. The delivery of therapeutic proteins, in particular, can be achieved by anchoring them to the bacterial surface, and various anchoring domains have been described for this application. Here, we investigated a new cell anchoring domain (CAD4a) isolated from a lactobacillal protein, containing repeats of a SH3_5 motif that binds non-covalently to peptidoglycans in the LAB cell wall. Using a fluorescent reporter, we showed that C-terminal CAD4a bound Lactobacillus fermentum selectively out of a panel of LAB strains, and cell anchoring was uniform across the cell surface. Conditions affecting CAD4a anchoring were studied, including temperature, pH, salt concentration and bacterial growth phase. Quantitative analysis showed that CAD4a allowed display of 105 molecules of monomeric protein per cell. We demonstrated the surface display of a functional protein with superoxide dismutase (SOD), an antioxidant enzyme potentially useful for treating gut inflammation. SOD displayed on cells could be protected from gastric digestion using a polymer matrix. Taken together, our results show the feasibility of using CAD4a as a novel cell anchor for protein surface display on LAB.